Dynamical and thermodynamical modulations on future changes of landfalling atmospheric rivers over western North America. Issue 17 (12th September 2015) - Gao, Yang; Lu, Jian; Leung, L. Ruby; Yang, Qing; Hagos, Samson; Qian, Yun
Abstract This study examines future changes of landfalling atmospheric rivers (ARs) over western North America using outputs from the Coupled Model Intercomparison Project Phase 5 (CMIP5). The result reveals a strikingly large increase of AR days by the end of the 21st century in the RCP8.5 scenario, with fractional increases between 50% and 600%, depending on the seasons and landfall locations. These increases are predominantly controlled by the super‐Clausius‐Clapeyron rate of increase of atmospheric water vapor with warming, while changes of winds that transport moisture in the ARs, or dynamical effect, mostly counter the thermodynamical effect of increasing water vapor, limiting the increase of AR events in the future. The consistent negative effect of wind changes on AR days during spring and fall can be linked to the robust poleward shift of the subtropical jet in the North Pacific basin.